JARGON IN MOBILE LEGENDS: BANG BANG - Andrew WiIliam Mussu; Sanerita Tresnawati Olii; Sarah Kamagi (Program Studi Pendidikan Bahasa Inggris, 2022)
Language continues to develop along with the development of the society itself which then results in a phenomenon appearing in the society, this phenomenon is the emergence of language variations within the community in the form of vocabulary that is only known by people who are in the community this phenomenon also occurs in Mobile Legend Bang Bang. The purpose of this research is to find out the form, and the contextual meaning of the jargon contained in Mobile Legends: Bang Bang. In this research, the researcher used the qualitative method. The data in the form of words and phrases were obtained from the smartphone especially the Mobile Legends: Bang Bang application, which is then recorded in digital notes. The data were analyzed using the qualitative data analysis technics by Donald Ary namely: organizing and familiarizing, coding and reducing, and enterpreting. The result showed that there were 44 jargons found in this research that is used by Mobile Legends: Bang Bang players namely: 16 in abbreviation form, 11 in word form, and 17 phrases form specifically, 8 in noun phrase, 8 in adjective phrase and 1 in verb phrase